2008
DOI: 10.2478/v10007-008-0010-7
|View full text |Cite
|
Sign up to set email alerts
|

N-Phthaloyl-glycine-hydroxamic acid as serum iron chelator in rats

Abstract: Major functions of iron, as an essential element for living organisms, are oxygen transport and its role in oxidative-reductive reactions that utilize its alternative ferrous--ferric states. Total body iron has to be strictly controlled because excess iron can be highly toxic, leading, through generation of reactive oxygen species (ROS), to iron overloading disorders (1, 2). Iron chelating therapy has long been the standard care for patients suffering from Thalassemias (anemias caused by mutation of globin gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…They can inhibit tumour cell growth too. 25 In the current work we studied the iron chelating activity of edible mushroom C. cibarius as a natural compound. Among all the body organs, liver is more susceptible to iron overloading damages; therefore we used liver tissue in a pathological study to show the iron overloading damages and to display the potential inhibitory effects of mushroom extract.…”
Section: Study Of Morphological Changesmentioning
confidence: 99%
“…They can inhibit tumour cell growth too. 25 In the current work we studied the iron chelating activity of edible mushroom C. cibarius as a natural compound. Among all the body organs, liver is more susceptible to iron overloading damages; therefore we used liver tissue in a pathological study to show the iron overloading damages and to display the potential inhibitory effects of mushroom extract.…”
Section: Study Of Morphological Changesmentioning
confidence: 99%
“…For related literature, see: Allen et al (1987); Antunes et al (1998); Barooah et al (2006a,b); Brana & Ramos (2001); Chandrasekhar et al (1999); Eugenio, et al (2004); Gö rner et al (2002); Khan & Ismail (2002); Matijević-Sosa & Cvetnić (2005); Neto et al (1993); Ng (1992); Shariat & Abdollahi (2004); Wang et al (1998); Xu et al (2005), Zhang et al (2004). Hydrogen-bond geometry (Å , ).…”
Section: Related Literaturementioning
confidence: 99%
“…Such phthalimide derivatives undergo photochemical reactions such as photochemical decomposition and decarboxylation (Görner et al, 2002). Moreover N-phthaloylamino acids and their derivatives possess a wide range of biological activities such as hypolipidemic (Neto et al, 1993) analgesic (Antunes et al, 1998) antimicrobial (Matijević-Sosa & Cvetnić, 2005) and DNA cleaving abilities (Brana & Ramos, 2001). Among the N-phthaloylamino acids, N-phthaloylglycine has been the most widely studied.…”
Section: Related Literaturementioning
confidence: 99%
“…mixed solvents, and it was established that the tautomeric equilibrium in 2-hdroxynaphthy lideneaniline schiff-bases depend on the polarity of the solvent, the acidity of the medium, the temperature, and the strength of the hydrogen bond. [6][7][8] Theoretical studies of tautomeric equilibrium in orhto-hydroxy schiff-bases have been reported. [9][10][11] Earlier [12][13][14] we have reported the cistrans isomerization of benzylideneaniline on addition of Eu(fod) 3 .…”
Section: Introductionmentioning
confidence: 99%